Method for testing permeability of rock core sample of salt rock
By injecting epoxy resin into the outside of the salt rock sample to form a protective layer and using 3D printing technology to make sample molds, the problems of corrosion and production difficulty of salt rock sample are solved, and the efficiency and accuracy of permeability testing are improved.
Patent Information
- Application Number
- CN202510474272.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2025-05-16
- Estimated Expiration
- 2045-04-16
AI Technical Summary
In the existing permeability test methods for salt rock samples, the salt content of the salt rock samples will corrode the testing instrument, and the sample production process is prone to failure, resulting in low yield and seriously affecting the detection efficiency.
3D printing technology is used to make hollow sample molds, and epoxy resin is injected outside the core sample to form a protective layer to protect the instrument and reduce the difficulty of sample production.
It effectively avoids the salt corrosion problem of salt rock samples, improves the success rate and testing efficiency of sample production, and improves the accuracy of permeability detection through correction factors.
Smart Images

Figure CN120009151A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of salt rock permeability testing, and in particular relates to a method for testing the permeability of a salt rock core sample. Background Art
[0002] Salt rock is internationally recognized as an excellent place for underground storage due to its low porosity, low permeability, and water-soluble mining. The permeability of the surrounding rock is an important indicator for geological storage. The professional instrument for measuring the permeability of core samples requires that the samples be columnar in shape. When applying confining pressure during the test, the existing triaxial seepage test device is used. At present, when making core samples in this field, large rock samples with fewer cracks and relatively complete rock blocks should be selected, and vertical coring machines should be used for drilling. During drilling, the rotation speed must be strictly controlled to ensure that the drill bit drills evenly and the core is intact. After coring, the cored coal sample is cut into a columnar salt rock sample using an automatic double-sided rock grinder, and polished to make the two end faces parallel, forming a columnar salt rock sample with a standard height-to-diameter ratio.
[0003] However, when the columnar salt rock sample is placed in the sample slot of the permeability test instrument, the salt contained in the sample will corrode the inner wall of the sample slot, causing damage to the instrument. In addition, due to the tectonic stress, the original structure and structure are severely damaged, resulting in structural changes such as fragmentation, wrinkling, and polished surface. As a result, the existing process of making columnar salt rock samples is very easy to fail, and the yield rate of the stone samples is not high, which seriously affects the efficiency of permeability testing. Therefore, the permeability test of salt rock samples is a difficult problem. Summary of the invention
[0004] In view of the above problems, the present invention provides a method for testing the permeability of a salt rock core sample, comprising: S1: Use a coring machine to drill and coring blocky salt rock to obtain core samples; S2: Using 3D printing technology, a hollow sample mold is printed according to the inner dimensions of the sample slot of the permeability test instrument, so that the inner dimensions of the sample mold are equal to the inner dimensions of the sample slot; S3: Load the core sample into the center of the sample mold, and inject a casting material between the core sample and the inner wall of the sample mold; after the casting material solidifies, a protective layer is formed on the outer side of the core sample; remove the sample mold, and then remove all or part of the protective layers at both ends of the core sample facing the test gas input pipe and output pipe, respectively, to obtain a sample block; S4: Place the sample block into the sample slot of the permeability test instrument, and the test gas is input and output from the exposed parts at both ends of the core sample to perform a permeability test.
[0005] In order to prevent the salt substances in the salt rock sample from corroding the instrument, the present invention makes a protective layer formed by a castable on the outside of the core sample, separates the core sample and the instrument sample slot, and protects the instrument sample slot. Since the outer shape of the protective layer is the same as the inner shape of the sample slot, the production requirements of the core sample are reduced, the sample production efficiency and success rate are improved, and the test efficiency of the salt rock sample is greatly accelerated. The core sample is in the shape of a rod, and the two ends of its central axis point to the two ends of the core sample respectively. During the test, one end of the core sample faces the input pipe of the test gas, and the other end faces the output pipe of the test gas, so that the test gas passes through the core sample.
[0006] Optionally, in step S1, a salt rock block sample to be tested is taken, and the salt rock block is drilled, cut and cored using an existing vertical drilling and coring machine, and then polished into a cylindrical or approximately columnar core sample; and then dried to remove moisture from the core sample.
[0007] Since there will be castables wrapped around the outside of the core sample, the core sample only needs to be made into an approximately columnar or cylindrical shape. The volume of the core sample can be smaller than the internal size of the sample slot of the testing instrument, and the requirements for the specific shape and size are not high.
[0008] Optionally, step S1 further includes the step of measuring the structure and size of the core sample. Specifically, the core sample is scanned using a laser and / or a 3D scanner to obtain three-dimensional size data of the core sample; and then image processing software (such as CAD software) is used to obtain the relationship between the cross-sectional area and the corresponding position in the direction of fluid flow in the core sample.
[0009] For example, for a core sample with a regular shape, the direction of the fluid flow inside it is parallel to the central axis of the core sample, and the cross section is perpendicular to the central axis; for a core sample with an irregular shape, the direction of the fluid flow inside it has an angle α with its own central axis, and the cross section perpendicular to the central axis also has an angle α with the effective seepage cross section.
[0010] Alternatively, the three-dimensional dimension data of the core sample is imported into the CAD software to measure the maximum length L of the core sample along the central axis. max , and the minimum cross-sectional area A min ; For a core sample with a regular shape, L max and A min It can be calculated by combining the three-dimensional size data with common formulas, L max is the effective seepage length, A min is the effective seepage cross-sectional area; For irregular shaped core samples, L maxis the distance between the upper and lower limits of the core sample, L is the effective seepage length of the core sample, and the inclination angle α of the irregularly shaped core sample is determined by the following formula: cosα=L / L max The effective seepage cross-sectional area A of the irregularly shaped core sample is determined by the inclination angle α and A min Determined using the following formula: A=A min / cosα Optionally, in step S2, the sample mold is a cylinder with a removable cover on the top, and all inner walls of the sample mold are smooth; the cover is provided with at least one through hole for injecting castable into the sample mold, and preferably, the position of the through hole corresponds to the space between the core sample and the inner wall of the sample mold.
[0011] Optionally, in step S3, the core sample is loaded into the sample mold and the lid is put on, with the upper and lower ends of the core sample respectively against the bottom surface of the sample mold and the lower surface of the lid to fix the core sample; the lid is sealed around to prevent the castable from overflowing; the castable is injected through the through hole on the lid; and the residual air in the sample mold is evacuated, and the castable is then naturally solidified to obtain a sample block.
[0012] The casting material is epoxy resin, which is transparent, not adsorbed by the core sample, and does not react with the core sample.
[0013] The permeability test method in step S4 is the same as that in the prior art, that is, the dried sample block is placed in the core holder (ie, the sample slot) of the gas permeability tester, the permeability test is performed on the sample block, and the test results are recorded.
[0014] In the present invention, in order to reduce the difficulty of making core samples, no requirement or low requirement is made for the smoothness and flatness of the side surfaces of the core samples (because the side surfaces are curved surfaces and are difficult to cut or grind), while the requirement for the flatness of the end surfaces at both ends of the core samples depends on the specific situation (because the difficulty of cutting or grinding the end surfaces is not high).
[0015] For example, for samples with good structural conditions and ample time, both ends of the core sample can be polished into a flat surface. The two ends of the core sample are flat and can be respectively fitted against the bottom surface of the sample mold and the lower surface of the cover. The sides of the core sample are wrapped with castables, and the end faces at both ends are not covered with a protective layer, or are only covered with a thin layer of protective layer. Before testing, the protective layers on the two end faces of the core sample are peeled off to expose the salt rock end faces for easy detection by the test gas.
[0016] For another example, for samples with poor structural conditions, if you are not careful when cutting or grinding, the samples may crack or break. In view of this situation, the present invention proposes the following solution.
[0017] Optionally, step S1 further includes grinding a flat portion at the center of both ends of the core sample, which is used to connect with the sample mold and receive or output the test gas during subsequent testing.
[0018] Further optionally, the areas of the end faces at both ends of the core sample are equal, the areas of the flat parts at both ends are also equal, and the ratio of the area of the flat parts to the area of the end faces of the core sample is not less than 0.5.
[0019] Further optionally, in step S2, a lower support platform protruding upward is provided at the center of the bottom of the sample mold, and an upper support platform protruding downward is provided at the center of the lower surface of the cover; The lower support platform is in the shape of an inverted truncated cone, the top surface diameter is larger than the bottom surface diameter, and the top surface of the lower support platform is used to contact and support the flat part at the center of the bottom end of the core sample; The upper support platform is in a truncated cone shape, with a top diameter smaller than a bottom diameter, and the bottom surface of the upper support platform is used to contact and support the flat portion at the top center of the core sample.
[0020] After the pouring and curing in step S3, except for the flat parts at both ends of the core sample, the rest of the parts, whether convex or concave, will be wrapped by the castable, and only the flat parts can expose the protective layer, which is used to receive or output the test gas during the test. Moreover, the two ends of the formed sample block each have a truncated cone-shaped opening, the diameter of the side of the opening away from the core sample is small, and the diameter of the side of the opening close to the core sample is large. After the test gas enters the opening, it can also diffuse along the inner wall of the opening, occupying most of the area on the cross section of the core sample as much as possible, and making the test gas form a form of diffusion toward the outside of the cross section and the effective diffusion direction, and then enter the core sample to continue to diffuse. After the test gas leaves the core sample, it gathers in another opening and then leaves the sample block.
[0021] In the traditional permeability test of salt rock samples, the cut and polished cylindrical samples are directly placed in the sample slot, and then confining pressure is applied to simulate the underground formation environment. The confining pressure acts directly on the sample surface. In the present invention, a protective layer is added to the core sample to completely wrap its side, and the epoxy resin has a certain strength after curing. The confining pressure first acts directly on the protective layer and then indirectly acts on the core sample. Therefore, the core sample of the present invention is slightly different from the prior art in terms of the pressure environment. During the test, the core sample may have some effect on the permeability due to the difference in the stress state. The present invention takes these deviations into consideration, and after repeated experimental comparisons, the protective effect of the protective layer on the side of the core sample on the permeability detection is integrated into a correction factor. When determining the permeability after the test, the correction factor needs to be introduced to correct the deviation and improve the accuracy of the detection.
[0022] The correction factor F1 is determined by the following formula: ; Wherein, D is the total average thickness of the protective layer of the sample block, in cm; B is the inner diameter of the sample tank, in cm; The corrected gas permeability is then determined by the following formula: ; Where: is the corrected gas permeability, in μm 2 ; Kg is the gas permeability, in μm 2 ; Q0 is the gas flow rate, in cm 3 / s;P o is atmospheric pressure, in Psi; μ g is the viscosity of the gas under atmospheric pressure and test temperature, in mPa·s; L is the effective seepage length of the core sample, in cm; A is the effective seepage cross-sectional area of the core sample, in cm 2 ; P1 is the upstream pressure, unit is Psi; P2 is the downstream pressure, unit is Psi.
[0023] The total average thickness D of the protective layer of the sample block is the difference between the diameter of the end face of one end of the sample block and the diameter of the end face of one end of the core sample. The volume of the core sample can be obtained by experiment. The core sample is assumed to be a standard cylinder, and its end face diameter is inferred from its volume. For example, the core sample is immersed in a liquid (the liquid is not absorbed by the core sample), and the change in the liquid volume before and after immersion is the volume of the core sample.
[0024] The thickness of the curved side of the sample block should not be too thin. If it is too thin, the gap between the sample mold and the core sample is small, and the castable is prone to uneven distribution, which has a negative impact on the test; if it is too thick, it also has a negative impact on the test. Therefore, in the study of the correction factor, the present invention limits the value of D / B to 1 / 5-1 / 10, which includes the vast majority of sample blocks. The sample blocks within this range have a high success rate in production and a stable and good test state. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a schematic diagram of a sample block of Example 1; Figure 2 Schematic diagram of the sample block of Example 2.
[0026] In the attached drawings, 1-core sample, 2-protective layer, 3-upper support platform, 4-lower support platform. DETAILED DESCRIPTION
[0027] Example 1 A method for testing the permeability of a salt rock core sample in this embodiment includes: S1: Use a coring machine to drill and coring blocky salt rock to obtain core samples; S2: Using 3D printing technology, a hollow sample mold is printed according to the inner dimensions of the sample slot of the permeability test instrument, so that the inner dimensions of the sample mold are equal to the inner dimensions of the sample slot; S3: Load the core sample into the center of the sample mold, and inject a casting material between the core sample and the inner wall of the sample mold; after the casting material solidifies, a protective layer is formed on the outer side of the core sample; remove the sample mold, and then remove all or part of the protective layers at both ends of the core sample facing the test gas input pipe and output pipe, respectively, to obtain a sample block; S4: Place the sample block into the sample slot of the permeability test instrument, and the test gas is input and output from the exposed parts at both ends of the core sample to perform a permeability test.
[0028] In step S1, a salt rock block sample to be tested is taken, and the salt rock block is drilled, cut and cored using an existing vertical drilling and coring machine, and then polished into a cylindrical or approximately columnar core sample; and then dried to remove moisture from the core sample.
[0029] Since there is still a castable material wrapped around the outside of the core sample, the core sample only needs to be made into a columnar or cylindrical shape, and the volume of the core sample is smaller than the internal size of the sample slot of the test instrument. The sample construction conditions of this embodiment are better, and both ends of the core sample are polished into a flat surface.
[0030] The step after step S1 also includes the step of measuring the structure and size of the core sample. Specifically, the core sample is scanned by using a laser and / or a 3D scanner to obtain three-dimensional size data of the core sample; and then image processing software (such as CAD software) is used to obtain the relationship between the cross-sectional area and the corresponding position in the direction of fluid flow in the core sample.
[0031] Import the three-dimensional dimension data of the core sample into the CAD software and measure the maximum length L of the core sample along the central axis. max , and the minimum cross-sectional area A min ; For the irregularly shaped core sample in this example, L max is the distance between the upper and lower limits of the core sample, L is the effective seepage length of the core sample, and the inclination angle α of the irregularly shaped core sample is determined by the following formula: cosα=L / L max The effective seepage cross-sectional area A of the irregularly shaped core sample is determined by the inclination angle α and A min Determined using the following formula: A=A min / cosα.
[0032] In step S2, the sample mold is a cylinder with a removable cover on the top, and all inner walls of the sample mold are smooth; a through hole is provided on the cover for injecting castable into the sample mold, and the position of the through hole corresponds to the space between the core sample and the inner wall of the sample mold.
[0033] In step S3, the core sample is placed in the sample mold, and the lid is put on. The upper and lower ends of the core sample are respectively against the bottom surface of the sample mold and the lower surface of the lid to fix the core sample; the lid is sealed around to prevent the castable from overflowing; the castable (epoxy resin) is injected through the through hole on the lid; the residual air in the sample mold is evacuated, and the castable is naturally solidified to obtain a sample block. The side of the core sample is wrapped with the castable, and the end faces at both ends are not covered with the protective layer 2, or are only covered with a thin layer of protective layer. Before testing, the protective layers at the two end faces of the core sample are peeled off to expose the salt rock end faces for easy acceptance of test gas detection.
[0034] Step S4 is specifically as follows: 1. Measurement conditions: Gas source: Helium cylinder 200psig (for testing), air / nitrogen cylinder 100psig (for operating pneumatic valves); Power supply: 90~250VAC, 50~60Hz; Ambient temperature: 25℃, fluctuation should be less than 1℃; Stable test principle parameters: 3sec, 0.01psi.
[0035] 2. Operation steps: (1) Set the helium pressure to 200 psig and the air / nitrogen pressure to 90 psig to ensure that there is no pressure loss along the entire line; select five calibration blocks for testing; test each calibration block in turn to generate a test baseline; (2) Enter the sample block number and its dry weight, effective seepage length L, effective seepage cross-sectional area A and other information in the rock sample information area, and test each sample block in turn.
[0036] 3. After the test is completed, calculate the volume of the core sample based on L and A, then calculate the pore volume, and record the test results.
[0037] The correction factor F1 is determined by the following formula: ; Wherein, D is the total average thickness of the protective layer of the sample block, in cm; B is the inner diameter of the sample tank, in cm.
[0038] Permeability indicates the ability of porous media to transmit fluid. When gas flows in porous media, according to Darcy's law of one-dimensional stable flow of gas, the corrected gas permeability is determined by the following formula: ; Where: is the corrected gas permeability, in μm 2 ; Kg is the gas permeability, in μm 2 ; Q0 is the gas flow rate, in cm 3 / s;P o is atmospheric pressure, in Psi; μ g is the viscosity of the gas under atmospheric pressure and test temperature, in mPa·s; L is the effective seepage length of the core sample, in cm; A is the effective seepage cross-sectional area of the core sample, in cm 2 ; P1 is the upstream pressure, unit is Psi; P2 is the downstream pressure, unit is Psi.
[0039] The corrected gas permeability of this embodiment is Kg'=Kg×F1=9.47×10 -9 ×0.885=8.38×10 -9 μm 2 .
[0040] On the same salt rock block sample to be tested in this embodiment, the existing method is used to drill, cut and core with a vertical drilling and coring machine, and then polish it into a standard cylindrical core sample, which is directly placed in the sample slot. The same test conditions as in this embodiment are used to test, and the gas permeability of the sample is calculated, and Kg=8.52×10 -9 μm 2 .
[0041] The error between Kg' in this embodiment and Kg obtained from the same sample source without a protective layer is: (8.52-8.38)×100% / 8.52=1.64%, which is relatively small.
[0042] Example 2 The permeability testing method of a salt rock core sample in this embodiment is the same as that in Embodiment 1, except that the structural condition of the salt rock block sample to be tested in this embodiment is poor, and step S1 also includes grinding a flat portion at the center of both ends of the core sample, which is used to dock with the sample mold and to receive or output the test gas during subsequent testing.
[0043] The areas of the end faces at both ends of the core sample are equal, the areas of the flat parts at both ends are also equal, and the ratio of the area of the flat part to the area of the end face of the core sample is 0.5:1.
[0044] In step S2, Figure 2 As shown, a lower support platform 4 protruding upward is provided at the center of the bottom of the sample mold, and an upper support platform 3 protruding downward is provided at the center of the lower surface of the cover; The lower support platform is in the shape of an inverted truncated cone, the top surface diameter is larger than the bottom surface diameter, and the top surface of the lower support platform is used to contact and support the flat part at the center of the bottom end of the core sample; The upper support platform is in a truncated cone shape, with a top diameter smaller than a bottom diameter, and the bottom surface of the upper support platform is used to contact and support the flat portion at the top center of the core sample.
[0045] The correction factor F1 is 0.885. The corrected gas permeability of this embodiment is Kg'=Kg×F1=12.60×10 -9 ×0.885=11.15×10 -9 μm 2 .
[0046] On the same salt rock block sample to be tested in this embodiment, the existing method is used to drill, cut and core with a vertical drilling and coring machine, and then polish it into a standard cylindrical core sample, which is directly placed in the sample slot. The same test conditions as in this embodiment are used to test, and the gas permeability of the sample is calculated, and Kg=10.67×10 -9 μm 2 .
[0047] The error between Kg' of this embodiment and Kg obtained from the same sample source without a protective layer is: (11.15-10.67)×100% / 10.67=4.50%.
[0048] Example 3 The permeability testing method of a salt rock core sample in this embodiment is the same as that in Embodiment 2, except that the ratio of the area of the flat parts at both ends of the core sample to the end surface area of the core sample is 0.8:1.
[0049] The correction factor F1 is 0.885. The corrected gas permeability of this embodiment is Kg'=Kg×F1=12.45×10 -9 ×0.885=11.02×10 -9 μm 2 .
[0050] The error between Kg' of this embodiment and Kg obtained from the same sample source without a protective layer is: (11.02-10.67)×100% / 10.67=3.28%.
[0051] Example 4 The permeability testing method of a salt rock core sample in this embodiment is the same as that in Embodiment 2, except that the ratio of the area of the flat parts at both ends of the core sample to the end surface area of the core sample is 0.4:1.
[0052] The correction factor F1 is 0.885. The corrected gas permeability of this embodiment is Kg'=Kg×F1=12.70×10 -9 ×0.885=11.24×10 -9 μm 2 .
[0053] The error between Kg' of this embodiment and Kg obtained from the same sample source without a protective layer is: (11.24-10.67)×100% / 10.67=5.34%.
[0054] Example 5 The permeability testing method of a salt rock core sample in this embodiment is the same as that in Embodiment 2, except that the upper support platform and the lower support platform of the sample mold are both cylindrical, so that the openings at both ends of the sample block are cylindrical.
[0055] The correction factor F1 is 0.885. The corrected gas permeability of this embodiment is Kg'=Kg×F1=12.84×10 -9 ×0.885=11.36×10 -9 μm 2 .
[0056] The error between Kg' of this embodiment and Kg obtained from the same sample source without a protective layer is: (11.36-10.67)×100% / 10.67=6.47%.
[0057] Table 1 Comparison of gas permeability errors after correction in the examples .
Claims
1. A method for testing the permeability of a salt rock core sample, characterized in that: include: S1: Use a coring machine to drill and coring blocky salt rock to obtain core samples; S2: Using 3D printing technology, a hollow sample mold is printed according to the inner dimensions of the sample slot of the permeability test instrument, so that the inner dimensions of the sample mold are equal to the inner dimensions of the sample slot; S3: Place the core sample in the center of the sample mold, and inject the casting material between the core sample and the inner wall of the sample mold; after the casting material solidifies, a protective layer is formed on the outer side of the core sample; Removing the sample mold, and then removing all or part of the protective layers at both ends of the core sample facing the test gas input pipe and output pipe, respectively, to obtain a sample block; S4: Place the sample block into the sample slot of the permeability test instrument, and the test gas is input and output from the exposed parts at both ends of the core sample to perform a permeability test.
2. The method for testing the permeability of a salt rock core sample according to claim 1, characterized in that: The test error caused by the thickness of the protective layer is classified as a correction factor and is determined by the following formula: ; Wherein, D is the total average thickness of the protective layer of the sample block, in cm; B is the inner diameter of the sample tank, in cm; The corrected gas permeability is then determined by the following formula: ; Where: is the corrected gas permeability, in μm 2 ; Kg is the gas permeability, in μm 2 ; Q0 is the gas flow rate, in cm 3 / s;P o is atmospheric pressure, in Psi; μ g is the viscosity of the gas under atmospheric pressure and test temperature, in mPa·s; L is the effective seepage length of the core sample, in cm; A is the effective seepage cross-sectional area of the core sample, in cm 2 ; P1 is the upstream pressure, unit is Psi; P2 is the downstream pressure, unit is Psi.
3. The method for testing the permeability of a salt rock core sample according to claim 1, characterized in that: In step S2, the sample mold is a cylinder with a removable cover on the top, and all inner walls of the sample mold are smooth; the cover is provided with at least one through hole for injecting castable into the sample mold, and the position of the through hole corresponds to the space between the core sample and the inner wall of the sample mold.
4. The method for testing the permeability of a salt rock core sample according to claim 3, characterized in that: In step S3, the core sample is placed in the sample mold, and the cover is closed, with the upper and lower ends of the core sample respectively against the bottom surface of the sample mold and the lower surface of the cover to fix the core sample; Seal the lid to prevent the castable from overflowing; inject the castable through the through hole on the lid; then evacuate the remaining air in the sample mold, and then allow the castable to solidify naturally to obtain a sample block.
5. The method for testing the permeability of a salt rock core sample according to claim 4, characterized in that: For samples with better structural conditions, both ends of the core sample are polished into flat surfaces. The two ends of the core sample are flat and respectively fit against the bottom surface of the sample mold and the lower surface of the cover. The sides of the core sample are wrapped with castables, and the end faces at both ends are not covered with a protective layer, or are only covered with a thin layer of protective layer. Before testing, the protective layers on the two end faces of the core sample are peeled off to expose the salt rock end faces, which are convenient for receiving or outputting test gas.
6. The method for testing the permeability of a salt rock core sample according to claim 4, characterized in that: For samples with poor structural conditions, step S1 also includes grinding a flat portion at the center of both ends of the core sample, which is used to connect with the sample mold and receive or output the test gas during subsequent testing.
7. The method for testing the permeability of a salt rock core sample according to claim 6, characterized in that: The areas of the end faces at both ends of the core sample are equal, the areas of the flat parts at both ends are also equal, and the ratio of the area of the flat parts to the area of the end faces of the core sample is not less than 0.
5.
8. The method for testing the permeability of a salt rock core sample according to claim 6, characterized in that: In step S2, a lower support platform protruding upward is provided at the center of the bottom of the sample mold, and an upper support platform protruding downward is provided at the center of the lower surface of the cover; The lower support platform is in the shape of an inverted truncated cone, the top surface diameter is larger than the bottom surface diameter, and the top surface of the lower support platform is used to contact and support the flat part at the center of the bottom end of the core sample; The upper support platform is in a truncated cone shape, with a top diameter smaller than a bottom diameter, and the bottom surface of the upper support platform is used to contact and support the flat portion at the top center of the core sample.
9. The method for testing the permeability of a salt rock core sample according to claim 1, characterized in that: The step between step S1 and step S2 also includes a step of measuring the structure and size of the core sample. Specifically, the core sample is scanned using a laser and / or a 3D scanner to obtain three-dimensional size data of the core sample; and then image processing software (such as CAD software) is used to obtain the relationship between the cross-sectional area and the corresponding position in the direction of fluid flow in the core sample.
10. The method for testing the permeability of a salt rock core sample according to claim 9, characterized in that: Import the three-dimensional dimension data of the core sample into the CAD software and measure the maximum length L of the core sample along the central axis. max , and the minimum cross-sectional area A min ; For a core sample with a regular shape, L max and A min It can be calculated by combining the three-dimensional size data with common formulas, L max is the effective seepage length, A min is the effective seepage cross-sectional area; For irregular shaped core samples, L max is the distance between the upper and lower limits of the core sample, L is the effective seepage length of the core sample, and the inclination angle α of the irregularly shaped core sample is determined by the following formula: cosα=L / L max The effective seepage cross-sectional area A of the irregularly shaped core sample is determined by the inclination angle α and A min Determined using the following formula: A=A min / cosα。
Citation Information
Patent Citations
Zero calibration method of core permeameter
CN101576468A
Man-made rock core with multi-pore structure and preparation method of man-made rock core
CN104089806A
Method for constructing special-shaped solid concrete structure through wet sprayed concrete technique
CN106747109A
Method for testing gas permeability of irregular loose rock sample
CN112304849A
Rapid testing and evaluating method for thickness of steel bar protection layer in uneven concrete surface
CN118729967A